2015
DOI: 10.1007/s10639-015-9398-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting teachers’ continuation of technology use in teaching

Abstract: This study was conducted to investigate the continuation of technology use in science and mathematics teaching of the teachers who attended a professional development program between 2010 and 2012. Continuation of technology use was hypothesized to be affected by the professional development program and by personal, institutional, and technological factors. Twelve teachers and three school leaders participated in the study. Data was collected through interviews. Findings showed that the continuation of technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 15 publications
4
64
0
6
Order By: Relevance
“…In addition, data from the completed surveys revealed that the factors determining the continuous use of technology in teaching can be categorized as follows: (a) professional development factors which comprise of the instructors' perceived values of the professional development program, and the opportunity for continuous learning; (b) personal factors which comprises of instructor belief, knowledge and skills, time and engagement; (c) institutional factors comprising the accessibility to technology, support from the management, and environment; (d) technological factors which comprises ease of use and effectiveness, where ease of use refers to the convenience, adequacy, reliability and user friendly of the technology, whereas effectiveness refers to the likelihood of the long tangible benefits for the institution, improved learning and communication. These factors were confirmed by Kafyulilo, Fisser, and Voogt's (2016) study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, data from the completed surveys revealed that the factors determining the continuous use of technology in teaching can be categorized as follows: (a) professional development factors which comprise of the instructors' perceived values of the professional development program, and the opportunity for continuous learning; (b) personal factors which comprises of instructor belief, knowledge and skills, time and engagement; (c) institutional factors comprising the accessibility to technology, support from the management, and environment; (d) technological factors which comprises ease of use and effectiveness, where ease of use refers to the convenience, adequacy, reliability and user friendly of the technology, whereas effectiveness refers to the likelihood of the long tangible benefits for the institution, improved learning and communication. These factors were confirmed by Kafyulilo, Fisser, and Voogt's (2016) study.…”
Section: Discussionsupporting
confidence: 58%
“…Overall, the key issues and challenges found to be significant in using ICT tools by teachers were: limited accessibility and network connection, limited technical support, lack of effective training, limited time, and lack of teachers' competency. Kafyulilo, Fisser, and Voogt (2016) investigated the factors affecting teachers' continuation of technology use in teaching. The findings of their study revealed that despite the challenges that all teachers in the sample encountered when using technology in their teaching (such as large classrooms, problems with electricity supply, lack of time, and lack of technology tools), the encouragement of school management was a critical factor in teachers' continuation of technology use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Successful dissemination also requires activities at school and municipality/ district levels (Eickelmann 2011;Petko et al 2015), as well as motivation and support from the school management (Kafyulilo et al 2016). The city's school administration was very proactive and persistent.…”
Section: Leadership For Second-order Changementioning
confidence: 99%
“…Islam and Grönlund (2016), for example, identified several implementation issues in education including contextual knowledge, teachers' professional development, sustainability, monitoring, evaluation and leadership. Kafyulilo et al (2016) found that integration of technological tools with the aim of developing traditional teaching practices into a continuation of ICT use and sustainable change is dependent on both support and engagement from the school management.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of low use of technology and continuation of technology use in teaching has been pursued from different perspectives (Kafyulilo, Fisser, & Voogt, 2016). Papanastasiou and Angeli (2008) examined the factors that affect teachers' efforts to teach with technology.…”
Section: Introductionmentioning
confidence: 99%